(untitled) (CIPEEX, 2022)
INTRODUCTION: SYPHILIS IS A HUMAN-ONLY, CURABLE SEXUALLY TRANSMITTED INFECTION CAUSED BY THE BACTERIUM TREPONEMA PALLIDUM, IN WHICH IT CAN PRESENT CLINICAL MANIFESTATIONS AND DIFFERENT STAGES. THE TRANSMISSION OF ACQUIRED SYPHILIS IS SEXUAL AND IN THE GENITAL-ANAL AREA, IN ALMOST ALL CASES. ACQUIRED SYPHILIS MAY HAVE ITS EVOLUTION DIVIDED INTO RECENT AND LATE. IN CONGENITAL SYPHILIS, THERE IS FETAL INFECTION VIA HEMATOGEN, USUALLY FROM THE 4TH MONTH OF PREGNANCY. AFTER TRANSPLACENTAL INFECTION, THE TREPONEMA GAINS THE UMBILICAL CORD VESSELS AND MULTIPLIES RAPIDLY THROUGHOUT THE FETAL ORGANISM, WHICH CAN GENERATE COMPLEX DISORDERS IN THE DEVELOPMENT OF THE FETUS, BECOMING A MAJOR HEALTH PROBLEM. IN BRAZIL, BETWEEN 2005 AND JUNE 2016, A TOTAL OF 169,546 CASES OF SYPHILIS WERE REPORTED IN PREGNANT WOMEN IN SINAN. IN THE LAST 11 YEARS, IN BRAZIL, THE INFANT MORTALITY RATE FROM SYPHILIS INCREASED FROM 2.4 / 100 THOUSAND BORN IN 2005 TO 7.4 / 100 THOUSAND LIVE BIRTHS BY 2015. OBJECTIVES: TO KNOW THE PROFILE OF SYPHILIS IN PREGNANT WOMEN IN THE MUNICIPALITY OF ANÁPOLIS FROM 2011 TO 2016, SEEKING TO KNOW THE REAL SITUATION OF THE MUNICIPALITY, THE STAGES OF HIGHER PREVALENCE, ADHERENCE TO TREATMENT AND THE MAIN AGE GROUP AFFECTED. METHOD: RETROSPECTIVE DESCRIPTIVE EPIDEMIOLOGICAL STUDY OF DATA EXTRACTED AND MADE AVAILABLE BY THE DEPARTMENT OF INFORMATICS OF THE UNIFIED HEALTH SYSTEM. WE ANALYZED CASES OF SYPHILIS IN PREGNANT WOMEN IN THE CITY OF ANÁPOLIS FROM 2011 TO 2016. DESCRIPTIVE STATISTICS WERE USED WITH ABSOLUTE AND RELATIVE FREQUENCY OF THE TOTAL NUMBER OF CASES FOR DATA ANALYSIS. RESULTS: IN BRAZIL, 157,513 CASES OF SYPHILIS OCCURRED IN PREGNANT WOMEN IN THE STATE OF GOIS, 4,895. THE MUNICIPALITY OF ANÁPOLIS REPRESENTED 5.87% OF CASES OF SYPHILIS ACQUIRED IN THE PERIOD FROM 2011 TO 2016, WITH A HIGHER PREVALENCE IN THE 2013 TO 2015 AND REDUCTION IN 2016. REGARDING SCHOOLING, INCOMPLETE SECONDARY EDUCATION HAS BEEN HIGHLIGHTED AMONG THE OTHERS. THE SELF-REFERRED ETHNICITY WAS BROWN AND THE AGE GROUP OF 20 TO 29 YEARS HAD A MORE EXPRESSIVE NUMBER. THE CLINICAL CLASSIFICATION OF SYPHILIS ACQUIRED IN PREGNANT WOMEN HAD A HIGHER INCIDENCE FOR PRIMARY AND LATENT SYPHILIS. REGARDING PRENATAL CARE, 82% PERFORMED; 63% WERE DIAGNOSED WITH SYPHILIS IN THIS PERIOD, 21% AT THE TIME OF DELIVERY, 13% AFTER CHILDBIRTH AND 3% IGNORED. IT WAS OBSERVED IN MOST CASES THAT THE TREATMENT WAS INAPPROPRIATE AND NOT PERFORMED BETWEEN THE PARTNERS. TWO CASES OF CONGENITAL SYPHILIS DEATH WERE RECORDED IN 2011 AND 2012 RESPECTIVELY. CONCLUSION: SYPHILIS HAS BEEN SHOWN TO BE AN INDICATOR OF VULNERABILITY, HIGHLIGHTING THE DEFICIENCY OF PRENATAL CARE QUALITY, WITH VERTICAL TRANSMISSION PERSISTING. THE NEED FOR INVESTMENT AND RESEARCH ON CURRENT CONDITIONS AND THE NEW DETERMINANTS OF INCIDENCE AND OUTCOME IS THUS PERCEIVED. TO MEET THE HEALTH MINISTRY’S OBJECTIVES OF CONTROLLING AND ERADICATING CONGENITAL SYPHILIS, ADEQUATE FOLLOW-UP OF THE TREATMENT OF PREGNANT WOMEN AND THEIR PARTNERS IS NECESSARY, WHICH REAFFIRMS THE IMPORTANCE OF RESEARCH STUDIES &NBSP;